NIPT - POTENTIAL TOOL FOR PGT FOLLOW UP. (April 2019) - Cram, David; Leigh, Don; Rechistsky, Svetlana; Kuliev, Anver
Abstract : Objective: Invasive procedures such as amniocentesis and CVS, in combination with karyotyping or molecular testing, are currently used to confirm PGT results of transferred embryos. However, some couples who have achieved a pregnancy following PGT-M are reluctant to use this confirmatory approach even though the risk of miscarriage and infection associated with fetal cell sampling is low. In this study, we investigate noninvasive prenatal testing (NIPT) as an alternative tool for PGT-M follow up. Materials and Methods: NIPT of the cell free fetal DNAwas performed for pregnancies at risk for a single gene disease using circulating single molecule amplification and re-sequencing technology (cSMART) to target the known parental mutations and genome-wide SNPs. Fetal genotypes were called based on the maternal plasma mutation ratios. Results: In preliminary studies of naturally conceived pregnancies undergoing testing for autosomal recessive conditions, fetal genotypes predicted by cSMART assay were concordant with invasive results in 4 of 4 cases (100%) of Wilson disease, 18 of 18 cases (100%) of PKU, 73 of 80 cases (91%) of autosomal recessive hearing loss and 98 of 100 cases (98%) of beta thalassemia. There was a strong association of low fetal DNA fraction and poor quality plasma samples with discordant NIPT results. In a further study, we performed NIPT follow up for a complicated PGT-M case for Fanconi Anemia with HLA matching. The case involved a couple who were both carriers of an identical FANCG deletion mutation. Following embryo testing by mutation analysis and linked STR analysis, 2 HLA matched and disease free (normal and carrier) embryos were transferred, resulting in a twin pregnancy. At 15 weeks gestation, cSMART analysis of the pregnancy plasma determined fetal DNA fractions of 14.2% and 6.6% for twin 1 and 2, respectively. The maternal plasma FANCG mutation ratio was measured at 46.2% (50% minus half the fetal fraction of twin 2), which was consistent with the presence of a carrier fetus (twin 1) and a normal fetus (twin 2). Additional retrospective studies of the WGA products from the transferred embryos using single molecule sequencing also confirmed the FANCG genotypes of the transferred embryos and a HLA match to the sick sibling. Conclusions: In proof of concept studies for autosomal recessive conditions, we demonstrate that NIPT can be successfully used to reliably and accurately determine fetal genotypes. NIPT has clinical utility as a safe alternative to invasive testing for confirmation of PGT-M cases that result in an ongoing pregnancy.